Healing the healers: A systematic review on the burden of secondary traumatic stress among healthcare providers - Betsy Sara Zacharias; Sheela Upendra (Journal of Education and Health Promotion)
Healthcare professionals (HCPs) are exposed to the traumatic and painful experiences of others as a part of their caring profession, which leaves them vulnerable to developing secondary traumatic stress (STS). It is an occupational hazard for those who provide direct patient care. Systematic review of quantitative studies on secondary traumatic stress among healthcare professionals was published in English between 2013 and 2023, using electronic databases: CINAHL, PubMed, MEDLINE, Global Health, PsychoInfo, and Google Scholar. The search produced 18 studies that explored secondary traumatic stress (STS) among healthcare professionals (HCPs) in the past 10 years (2013–2023). Most studies identified a high level of STS among HCPs. The Secondary Traumatic Stress Scale is the tool widely used to measure STS. Emotional exhaustion, exposure to patients’ deaths, multiple exposures to trauma, and a lack of job satisfaction predicted STS, whereas self-care, sports, social support, and debriefing remained protective factors. There has been evidence of secondary traumatic stress in healthcare professionals. The synthesis of data that are currently available highlights the emotional and psychological costs that care providers may incur from ongoing exposure to traumatic situations, underscoring the necessity of taking preventative action to address and lessen the effects of secondary traumatic stress.